Jesus nasceu e morreu : nada maior nem mais justo pode ser pensado : a cristologia de Anselmo de Aosta - Romio, Jocimar (2016)
The present study aims to bring back the contribution of the theological reflection of Anselmo de Aosta (1033-1109), especially with regard to the subject of the Word’s incarnation and Jesus death, core of the Christology. Thus this research is divided into three chapters. The first one presents a study of the context where Anselmo lived and shows the methodological anselmian perspective, especially by the audacity to write only through the reason (ratione sole), as if putting aside any authority, but always by linking faith and reason (fides et ratio). Within the faith program that searches for the comprehension (fides quaerens intellectum) God will be shown as that than which nothing greater can be conceived (id quo maius cogitari nequit), the single argument (unum argumentum) of God’s existence, presented in the work Proslogion, connecting it to the called essencial reasons (rationes necessariae) for a possible Christology (remoto Christo). After exposing some Christological ideas in the Church's ancient tradition, the second chapter carries out an investigation on the topic of the need for satisfaction (satisfactio) in light of the justice mainly through the works Cur Deus Homo and Epistola de Incarnatione Verbi. The possibility, the need and the form of redemption are relevant and useful aspects in order to understand the anselmian Christology. Finally, the third paragraph presents and reflects more directly the Anselmo’s theory of satisfaction, by relating justice, mercy and love, as well as in a Christological tri-perspective, bringing together the freedom and the will of Jesus Christ and his obedience to the Father's designs. Fundamental concepts in this chapter are also the righteousness (rectitudo) and will (voluntas) in view of perfect happiness (beatitude).